Side-Gigs of the Literati: Humanitarianism at its Best - Yvonne Captain (Revista Internacional de Cooperación y Desarrollo)
Resumen: In 2013, a Dominican lower court issued Judgment 168-13, deciding that many of the country’s population were not citizens. It was a clear act of purging people of Haitian descent. The Judgment was made against Juliana Deguis, hence she became the “poster child” for a legal, cultural, and humanitarian struggle in existence for decades, indeed more than a century in that nation. Humanitarianism aided in that difficult situation. As a student of south-south relations, and with a focus on literary superstars, I show how citizens of developing countries sometimes create their own solutions.